UNTANGLING THE REQUIREMENT OF GOOD FAITH IN THE DERIVATIVE ACTION IN COMPANY LAW (Part 2) - Maleka Femida Cassim (Obiter, 2018)
A crucial prerequisite for a derivative action is that the applicant must be acting in good faith in terms of section 165(5)(b)(i) of the Companies Act 71 of 2008 in order to obtain the leave of the court to bring the proposed derivative action. Both the Supreme Court of Appeal and the High Court have recently made important pronouncements of legal principle on the approach that the courts would take to the determination of good faith for the purposes of the statutory derivative action under section 165 of the Companies Act. These judicial findings relate not only to the complex issue of how to prove good faith but also to the meaning and content of the requirement of good faith. The courts have now reached a crossroads in delineating the content of good faith and how it is to be proved. This two-part series of articles critically evaluates these judicial pronouncements. While the focus of these articles is mainly on the tangled requirement of good faith, relevant judicial findings on the other prerequisites for a derivative action under section 165(5)(b) read with (7) and (8) of the Companies Act are also discussed. A comparative approach is adopted which takes into account the jurisprudence developed in Australia, Canada and Singapore. The first article in this series of two articles discussed the test of good faith. This article focuses on the proof of good faith.